Instructional materials in structural approach to reading comprehension - Librojo, Sonia (Salita) 1937- ([Quezon City s.n.], 1973)
Approaches to help develop awareness of inter-structure relationship or efficient comprehension of the paragraph or longer units of discourse in English by high school students were presented in this seminar paper. The reading exercises are mainly concerned with developing cognizance of the structure of the paragraph as a strategy for efficient comprehension. The chapter which contains the instructional materials presents different types of exercises focused on structural skills in reading paragraph and are designed to hasten development of structural control of the target language which will therefore help the reading improvement of learners.
Thesis (M.A.T.)--University of the Philippines.
Keywords: Reading (Secondary education).